Integrasi Manajemen Perubahan pada Proyek Lean Six Sigma dalam Peningkatan Mutu dan Kinerja Perusahaan - Ayesha Gilang Prahara; Catharina Badra Nawangpalupi (Universitas Katolik Parahyangan, 2021)
PT X is a small enterprise producing various types of jute fabric products. As a traditional business, the company still largely rely on the handiness and crafting skills from their workers. Whilst the business competition increases, PT X requires to strengthen the business by improving product quality in an efficient way. Besides high level of defects, PT X has also non-value-added activities in their production resulting in high overtime hours of their workers. Although PT X considers the overtime is acceptable to achieve the production target, there is room for improvement to reduce the defects as well as to shorten the production lead time. This paper aims to tackle the inefficiency and quality of the company. Lean six sigma is proposed to improve the condition and change management is implemented to ensure the commitment and participation of all staff for the success of change. Hence, this paper proposes the combination of change management and lean six sigma to improve production quality, lead time and staff participation. Combining DMAIC methods with change management, a methodology called DMA(C)IC is used with the middle C is for change. The implementation of the integration between change management in lean six sigma has resulted in the reduced number of defects and shorter lead time and the awareness of the workers to improve their working behavior.